2003
DOI: 10.1021/ma021510b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Reactivity on the Molecular Weight, Polydispersity, and Degree of Branching of Hyperbranched Poly(arylene ether phosphine oxide)s

Abstract: Synthesis of hyperbranched poly(arylene ether phosphine oxide)s, HB PAEPOs, from bis(4-fluorophenyl)(4-hydroxyphenyl)phosphine oxide, 1a, in the presence of a series of core molecules with systematically altered reactivity of the aryl fluoride groups provides polymers with molecular weights, MWs, controlled by the concentration of the core molecule, and narrow polydispersity indices, PDIs. Polymers with number-average molecular weights ranging from 3270 to 8100 Da, and PDIs as low as 1.25 have been prepared. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 38 publications
6
51
0
Order By: Relevance
“…Fossum et al have shown that copolymerization of an AB 2 monomer with multifunctional C f cores, where the reactivity towards A of the C group is higher than that of the B group, permits to reduce dispersity of the resulting hyperbranched polymers. 29 Similar results were obtained by Ramakrishnan et al for the copolymerization of AB 2 with a higher reactivity core molecule. 30 In an attempt to reduce dispersity further, use of slow feeding combined with higher reactivity core can be used.…”
Section: Scheme 2 Preparation Of Hyperbranched Thiol-yne Polymers Bysupporting
confidence: 80%
See 2 more Smart Citations
“…Fossum et al have shown that copolymerization of an AB 2 monomer with multifunctional C f cores, where the reactivity towards A of the C group is higher than that of the B group, permits to reduce dispersity of the resulting hyperbranched polymers. 29 Similar results were obtained by Ramakrishnan et al for the copolymerization of AB 2 with a higher reactivity core molecule. 30 In an attempt to reduce dispersity further, use of slow feeding combined with higher reactivity core can be used.…”
Section: Scheme 2 Preparation Of Hyperbranched Thiol-yne Polymers Bysupporting
confidence: 80%
“…Note that increasing molecular weight by increasing monomer concentration leads to higher Đ, as expected from theory and previous reports in the literature. 17,28,29,39 A monomer concentration of 1.1 M was found to give a good combination of control over molecular weight and molecular weight distribution, with very high degree of branching. These conditions were used to investigate the effect of mole fraction core molecule, and conduct a more detailed study of polymer conformation and molecular weight using multidetector SEC.…”
Section: Scheme 2 Preparation Of Hyperbranched Thiol-yne Polymers Bymentioning
confidence: 97%
See 1 more Smart Citation
“…Bernal et al [167] The substantial increase in Ð values with the increase of AB 2 in the ratio of AB: AB 2 was attributed to the greater number of end groups present in the growing polymer chains, thus favoring the reaction of monomer with growing polymer rather than starting a new polymer chain. Fossum and coworkers also observed that the effect of reaction temperature was not that significant for 5 mol% of core molecule in comparison to that observed at 3 mol%.…”
Section: Hyperbranched Poly(aryl Ether)s With a Phosphine Oxide Moietymentioning
confidence: 99%
“…The physical properties of hyperbranched polymers depend on the chemical composition, molecular weight, molecular weight distribution, and degree of branching (DB), and therefore it is desirable to develop a new controlled polymerization method that can afford polymers with defined molecular weight and low polydispersity. Slow addition of monomers to a core molecule [10][11][12][13][14] and the use of highly reactive core molecules [15] have been reported. In both cases, however, the deviation of the observed molecular weight from the calculated value, based on the feed ratio of the monomer to the core ([monomer] 0 /[core] 0 ), increased and the polydispersity broadened when attempts were made to synthesize higher-molecular-weight polymer.…”
Section: Introductionmentioning
confidence: 99%